Integrasi Nilai-nilai Multikultural dalam Pembelajaran Akidah Akhlak - ,, Faizah (As-Sibyan, 2018)
This study aims to discuss the concept of integration of multicultural values ​​in the learning of moral character in MI Tarbiyatut Tholabah Kranji Paciran Lamongan, the implementation of Akidah Akhlak that is integrated with multicultural values and the implications. Method: This research is a qualitative descriptive research, using sociology approach with research subjects of madrasah headmaster, Akidah Akhlak teacher, teacher and student council. Results: 1) the concept of integration of multicultural values ​​at MI Tarbiyatut Tholabah emphasizes inclusive and mutual respect among people. 2) Implementation of intellectual learning is integrated through the planning (mapping KD, syllabus, RPP, methods and learning media that are integrated with multicultural values). 3) The implications are the mutual appreciation of language diversity, respect for differences in ability, respect for age differences, and respect for differences in social conditions.